Work Posture Evaluation of Manual Onion Finishing After Mechanical Peeling in a Food Processing Industry - Rizki Alfi; Rahma Sawitri; Khairun Nadiyah; Maryam (Jurnal Sistem Teknik Industri, 2025)
Automation is increasingly applied in food-processing industries to enhance production efficiency. However, in onion-processing operations, peeling machines often fail to completely remove the outer skin, requiring workers to perform manual re-peeling to ensure raw-material quality. This task involves repetitive hand motions and forward-leaning postures, which may contribute to musculoskeletal strain. This study aims to evaluate the work posture of manual onion re-peeling workers using the Nordic Body Map (NBM) and Rapid Upper Limb Assessment (RULA) methods. Four workers participated in the study through direct observation, photo documentation, and questionnaire administration. NBM results indicated that the most frequent complaints occurred in the the shoulders, upper arms, elbows, forearms, wrists, and lower back. The average RULA score of 6 indicates a high-risk posture requiring prompt ergonomic intervention. The strong alignment between NBM and RULA findings reinforces the accuracy of the ergonomic diagnosis. This study highlights the need for ergonomic improvements such as workstation height adjustment, provision of lumbar-supported seating, micro-break scheduling, and simple tool redesign to reduce MSD risks and improve productivity in food-processing operations.